110k views
2 votes
Helppppppppppppppppppp please

Helppppppppppppppppppp please-example-1

1 Answer

5 votes

Answer:


\sqrt[]{(x+8)/(4)}-3

Explanation:


g(x)=4(x+3)^2-8

First rewrite
g(x) as y


y=4(x+3)^2-8

Now swap y and x


x=4(y+3)^2-8

Add 8 on both sides.


x+8=4(y+3)^2-8+8


x+8=4(y+3)^2

Divide by 4.


(x+8)/(4) =(4(y+3)^2)/(4)


(x+8)/(4)=(y+3)^2

Extract the square root on both sides.


\sqrt[]{(x+8)/(4)}=\sqrt[]{(y+3)^2}


\sqrt[]{(x+8)/(4)}=y+3

Subtract 3 on both sides.


\sqrt[]{(x+8)/(4)}-3=y+3-3


\sqrt[]{(x+8)/(4)}-3=y

User CMPerez
by
5.4k points